Improving Spelling Proficiency in Filipino through Word-Paragraph Discrimination Strategy (LITPAM, 2025)
One common dilemma in the Filipino language is the poor spelling skills among students. This is reflected in their written outputs and even posts in social media. Good spelling of words in a language is a manifestation of linguistic familiarization and even mastering its vocabularies. This action research study explored the spelling gaps among high school students. A primary goal is to find out the spelling proficiency problem as evidence of claimed poor spelling skill and an intervention is applied. A quasi-experimental method was used in this study. Pre-test and post-test were all administered to two groups of respondents. A word-paragraph discrimination strategy (WPDS) was used as an intervention for the experimental group. The basis for the standard spelling and rules was anchored from the Orthography of Filipino released by the Komisyon sa Wikang Filipino (KWF). The results revealed that in the pre-test, both groups gained poor results which support the observed poor spelling proficiency of the students. Meanwhile, the result in the post-test revealed a big difference for both groups. The control group did not meet significant progress while the experimental group had gained excellent results which signifies great improvement. The intervention used is proven effective and can help in improving the spelling proficiency of the students in Filipino. Strategy such as WPDS promotes a metalinguistic awareness of maintaining the standard of a language, consonantly, acclimating students in the conventions of spelling and vocabularies.